AAGBS Annual Report 2021: AAGBS KPI & PI achievements (thrust 4) - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2021)
Thrust 4 industrial linkages & international (JIA) by leader Dr. Arlinah Abd Rashid